Planeación Financiera aplicada en la Importadora MINASUR CIA. LTDA. de la Ciudad de Loja. Período 2024-2028 - Azuero Castillo, Susana Salomé (2025)
The Curricular Integration Project titled "Financial Planning Applied to Importing company MINASUR CIA. LTDA. in Loja (2024-2028)" aims to support company partners in making strategic business decisions through economic, financial, and strategic diagnosis, as well as cash flow and profit planning. The goal is to minimize future risks, increase profitability, and ensure long-term company sustainability. For the first specific objective, financial statements from 2022-2023 were analyzed to evaluate variations in financial accounts. Financial indicators were used to assess liquidity, solvency, management efficiency, and profitability. Additionally, a SWOT analysis was conducted, yielding 2.77 points for internal factors and 2.57 points for external factors, indicating a positive internal state and strong positioning in the mining sector. For the second objective, sales and purchase forecasts were made based on monthly data from 2023, applying a 10% growth rate. This resulted in an increase in cash budget from $383,666.53 in 2024 to $2,769,806.80 by 2028. Subsequently, pro forma financial statements (balance sheet and income statement) were prepared using the percentage-of-sales method, internal policies, and horizontal analysis. The projected net income was $359,000.29 for 2024, increasing to $715,939.88 by 2028. Finally, for the break-even analysis, costs and expenses were classified as fixed or variable, determining that the minimum sales required to break even in 2024 was $1,315,646.45, while in 2028, it was $1,307,796.10, ensuring financial balance in operations.